Chasing the Unknown the Quest for Decarbonization (Global Journal of Science Frontier Research, 2024)
Isn t it noteworthy that an agreement reached in the1990 sto combat climate change has triggered to this day so much conflict with strong deniers of the existence of the problem and militant supporters of the need to address the issue Are the temperature increases over the last decade an indication that global warming is finally catching up with us Or are the paltry changes in our energy matrixes and policies an indication of failure of the decarbonization effort or the inherent limitations of human endeavors to address emerging global issues Perhaps both obviously contradictory postures may signal that the discussion has become overly ideologized and thus impervious to proper diagnoses that provide technically sound answers for effective response to the issue